Answer:
Step-by-step explanation:
<h3>Given</h3>
- h(x) = (f ο g)(x)
- h(x) =
- f(x) =
<h3>To find</h3>
<h3>Solution</h3>
<u>We know that:</u>
<u>Substitute x with g(x) and solve for g(x):</u>
- =
- x + 5 = g(x) + 2
- x + 3 = g(x)
- g(x) = x + 3
Answer:
Step-by-step explanation:
The null hypothesis is usually the default statement while the alternative hypothesis is its opposite and usually tested against the null hypothesis.
In this case study, the null hypothesis is u = 21%/0.21, the percentage is not different among residents in Sonoma County and is equal to 0.21.
While the alternative hypothesis is u =/ 0.21, the percentage is different among residents in Sonoma County; not equal to 0.21
Answer:
2.7
Step-by-step explanation: